Supplementation of Psidium guajava (Guava) Fruit Polysaccharide Attenuates Paracetamol-induced Liver Injury by Enhancing the Endogenous Antioxidant Activity - ASPALILAH ALIAS; FAIZAH OTHMAN; ABDUL RASHID LI; AQILAH KAMARUDDIN; RAFIZUL YUSOF; FARIDA HUSSAN (Penerbit Universiti Kebangsaan Malaysia, 2024)
Non-Indexed Publication